EJ Moran Campbell - An Appreciation - Norman L Jones (Canadian Respiratory Journal, 2004)
Dr EJ Moran Campbell, Founding Chairman and R Samuel McLaughlin Professor of Medicine at McMaster University, 1968 to 1975, died on April 12, 2004, following a long battle with colon cancer. He was an outstanding scientist, physician and educator, achieving a worldwide reputation as the foremost clinical respiratory physiologist of his generation who changed how respiratory medicine was taught and practiced. He was elected a fellow of the Royal Society of Canada in 1983 and appointed an officer of the Order of Canada in 2001. He suffered intermittently from a mood disorder, which was a great burden. He published an extraordinarily insightful book on his experiences with this debilitating illness titled Not Always on the Level (1).